Pengaruh Pola Struktur Geologi terhadap Karakteristik Getaran Tanah Akibat Peledakan pada Tambang Batugamping - Yuliadi Yuliadi; Ridho K. Wattimena; Ganda M. Simangunsong; Nuhindro Priagung Widodo; Dhia Fahri H (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Ground vibrations generated by blasting at limestone quarries may affect surrounding infrastructure and the environment. Although blasting vibration is commonly evaluated based on distance and explosive charge per delay, the influence of geological structures on vibration propagation is often overlooked. This study aims to evaluate the effects of geological structure patterns and orientations on blasting-induced ground vibration characteristics. A quantitative approach was applied using primary data from blast vibration measurements and geological structure mapping via the scanline method, supported by secondary data including geological maps and building vibration resistance classifications based on SNI 7571:2010. Vibration characteristics and site-specific attenuation parameters were analyzed using the Scale Distance (SD) and Peak Vector Sum (PVS) relationship. The results show that joint orientations predominantly trend N310°E–N320°E and are controlled by a west–southeast–trending normal fault. A strong correlation in the PVS–SD relationship confirms the suitability of the scale distance method. Measurements parallel to the fault orientation yield lower PVS values than predicted, indicating vibration attenuation, whereas perpendicular measurements result in higher PVS values, indicating vibration amplification. These findings highlight the importance of geological structure orientation as a key factor in site-specific blasting design and vibration control. Abstrak. Kegiatan peledakan di tambang batugamping menimbulkan getaran tanah yang dapat memengaruhi lingkungan dan infrastruktur. Besarnya getaran umumnya dipengaruhi oleh jarak dan muatan bahan peledak per delay, namun metode konvensional belum sepenuhnya mempertimbangkan peran struktur geologi. Penelitian ini bertujuan menganalisis pengaruh pola dan orientasi struktur geologi terhadap karakteristik getaran peledakan dengan pendekatan kuantitatif. Data primer meliputi pemetaan struktur geologi menggunakan metode scanline dan pengukuran getaran, sedangkan data sekunder berupa peta geologi dan klasifikasi ketahanan bangunan menurut SNI 7571:2010. Analisis getaran dilakukan menggunakan hubungan Scale Distance (SD) dan Peak Vector Sum (PVS). Hasil penelitian menunjukkan arah umum kekar N310°E–N320°E yang dikontrol oleh sesar normal berarah barat–tenggara. Hubungan PVS–SD menunjukkan korelasi kuat antara jarak dan getaran. Getaran yang sejajar dengan arah sesar mengalami peredaman, sedangkan getaran yang memotong arah sesar mengalami penguatan. Hal ini menegaskan bahwa orientasi struktur geologi berperan penting dan perlu dipertimbangkan dalam perencanaan serta pengendalian peledakan.